2021
DOI: 10.1051/e3sconf/202124411024
|View full text |Cite
|
Sign up to set email alerts
|

Education policy: the impact of e-learning on academic performance

Abstract: The high use of web systems in learning implies that e-learning is becoming a common successful learning method in wider academic contexts. In order to enhance and support schooling and literacy, e-learning includes leveraging information and communication technology (ICT). The purpose of the analysis was to determine the correlation between e-learning and the academic achievement of students in higher learning. A set of 150 author’s observational studies, carried in Russian educational institutions (both in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
(7 reference statements)
2
10
0
Order By: Relevance
“…It means, e-learning standard if poor can affect performance, however, if strong can cultivate better academic performance. Another research was conducted by Zolochevskaya et al (20) where data was collected from 150 studies conducted by Russian educational institutes. The acquired data revealed that the absence of effective ICT facilities could significantly affect the learning and performance of the students to a considerable degree.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…It means, e-learning standard if poor can affect performance, however, if strong can cultivate better academic performance. Another research was conducted by Zolochevskaya et al (20) where data was collected from 150 studies conducted by Russian educational institutes. The acquired data revealed that the absence of effective ICT facilities could significantly affect the learning and performance of the students to a considerable degree.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Prior achievement (pre-university mathematical performance) and self-efficacy attitudes were found to be significant predictors of performance on the university mathematics course, according to the researchers. In the case of E-learning, Zolochevskaya et al [47] back up this assertion by revealing that ICT has a significant statistically advantageous effect on students' academic progress.…”
Section: Regression Analysis On Mathematics Anxiety Learning Engageme...mentioning
confidence: 99%
“…According to Zolochevskaya et al (2021), ICT has a substantial positive effect on the total success of students in universities. Latest research confirms the overall positive attitude of students and faculty members towards the use of online and e-learning modules/methods (Gerasimova et al, 2018).…”
Section: Online Learning and Teaching Becomes Crucialmentioning
confidence: 99%